A review of Open Channel Design for Mine Dewatering System Based on Environmental Observations - Ainul Saputra; A. A. Inung Arie Adnyano; Bayurohman Pangacella Putra; Agung Dwi Sutrisno; Akhmad Zamroni; Amir Machmud (CV FOUNDAE, 2023)
The purpose of mine dewatering system is to control runoff water that enters mine openings so that the mining process is not disturbed. The rainfall discharge (Q) is 0.0951 m³/second and the runoff discharge (Q) is 0.69 m³/second, making the total mining discharge entering the location 0.781 m³/second. The open channel design has dimensions of Channel wall slope (α) = 60°, Water depth (h) = 0.73 m, Channel depth (d) = 0.83 m, Channel base width (B) = 0.73 m, Surface width (b) = 1.57 m, Wet cross-sectional area of channel (A) = 0.92 m², and Channel wall length (a) = 0.97 m. The sedimentation pond has the following dimensions and compartments: Total length (l) = 104 m; width (b) = 8 m; depth (H) = 4 m; partition width = 4 m; partition depth = 4 m; partition length = 7 m. It consists of 3 compartments: conditioning compartment, separation between solids and mine water, and flow with an area of 277 m² per compartment. The sedimentation pond volume is 3094 m³ with a total area of 830 m². The results of the study obtained information that to control runoff water entering mine openings, a pond capacity as a settling site was needed of more than 3094 m³ with a maximum dredging time of settling pond particles that can be done once every 10 months.